2016
DOI: 10.1002/pa.1604
|View full text |Cite
|
Sign up to set email alerts
|

Public values and administrative reforms in French health care

Abstract: Public value appears to be reborn out of the ashes of earlier failed new public management (NPM)-driven policies in health care. It advocates greater consultation of the civic society and autonomy of public managers in decision-making. In France, the 2009 Hospital, Patient, Health, and Territory law recentralized the health system and strengthened the central government to restore consistency in policy implementation and address earlier NPM shortcomings. The 2014 Health Project heralds a phase of policy hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Customer satisfaction (CS) in tourism is used both as a subjective and objective parameter. As a subjective parameter, it relates to customer needs and emotions while as an objective parameter it shows product and service features (Simonet, 2017). However, there is inadequate literature that can provide all the attributes which drives CS in tourism research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Customer satisfaction (CS) in tourism is used both as a subjective and objective parameter. As a subjective parameter, it relates to customer needs and emotions while as an objective parameter it shows product and service features (Simonet, 2017). However, there is inadequate literature that can provide all the attributes which drives CS in tourism research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, consolidated research data in the Indian context seems to be lacking. The results can provide information about the size of the problem and the findings can be used to design health welfare policies for healthcare professionals, develop administrative reforms, intervention strategies for this group and possibly other specialties as well, thereby ensuring a higher quality of life (QoL) and making the work environment safer, healthier without compromising the productivity and profit (Simonet, 2017; Simonet, 2018). The study was undertaken with the following aims: (a) to study the incidences of WMSDs experienced by healthcare workers working in hospitals of India by Nordic Musculoskeletal Questionnaire (NMQ), (b) to quantify the psychosocial stress experienced by nurses through Organizational Role Stress Scale (ORS‐Scale) and Modified Nursing Stress Scale (MNSS), (c) to quantify the psychosocial factors and their possible association with WMSDs in doctors by Re‐modified Work‐style instrument, (d) to evaluate the intensity of pain pre and postexposure of work in doctors by Visual Analogue Scale (VAS), (e) to ascertain the QoL among nurses by Quality of Life Questionnaire (WHOQOL‐BREF).…”
Section: Introductionmentioning
confidence: 99%
“…However, consolidated research data in the Indian context seems to be lacking. The results can provide information about the size of the problem and the findings can be used to design health welfare policies for healthcare professionals, develop administrative reforms, intervention strategies for this group and possibly other specialties as well, thereby ensuring a higher quality of life (QoL) and making the work environment safer, healthier without compromising the productivity and profit (Simonet, 2017;Simonet, 2018). The study was undertaken with Finally, the study concluded addressing a vital issue of healthcare industry opining job redesign, implementation of policy-driven interventions in the attenuation of WMSDs in order to enhance productivity and better QoL.…”
Section: Introductionmentioning
confidence: 99%